Provenance and paleoenvironmental significance of sediments in the Beipo seamount of the northern South China Sea during the last deglaciation - Tian, Xu; Zhang, Xilin; Wang, Jinli; Sun, Zhilei; Liu, Ming; Zhao, Jinhuan; Zhang, Lin; Fan, Dejiang; Xu, Fangjian (Frontiers in Marine Science, 2023)
The sedimentary processes of seamount regions are closely related to climate change and ocean evolution. The clay minerals, grain size and 14C ages of core SCS18-1, which was collected from the Beipo seamount in the northern South China Sea (SCS) were analyzed to discuss the provenance and paleoenvironmental conditions during the last deglaciation. The sediments of core SCS18-1 are dominated by clayey silt, which is mainly composed of illite (55.2~62.1%) and chlorite (17.1~22.5%), with subordinate kaolinite (9.5~12.6%) and smectite (7.3~15.1%). The illite chemical index and illite crystallinity indicate strong physical weathering conditions. The results of the end-member modeling algorithm (EMMA) suggest that the sediments of core SCS18-1 consist of three end-members containing EM1 (0.98 μm), EM2 (9.29 μm) and EM3 (44.19 μm), with average contents of 3%, 66% and 31%, respectively. The finest endmember represents fluvial mud, the middle and coarsest endmembers are considered fluvial fine silt and eolian dust, respectively. The mean grain size is mainly controlled by the coarser fraction EM3. Based on the clay minerals, grain size and SEM analysis, we can conclude that since the onset of the last deglaciation (16.1 ka BP), the sediments of core SCS18-1 mainly originate from fluvial input, and eolian material also contributed to the sediments. The clay mineral assemblages of core SCS18-1 are stable and originate mainly from Taiwan. Additionally, the Pearl River appears to be a secondary contributor of clay minerals. Further, the Luzon Islands only account for a small proportion. Major kaolinite and moderate illite and chlorite are thought to originate from the Pearl River, predominant illite and chlorite from Taiwan, and principal smectite from the Luzon Islands. Both the relative content of EM1+ EM2 and the illite chemical index effectively represent the variation of East Asia summer monsoon (EASM) strength. Meanwhile, the relative content of EM3 effectively represents the East Asian winter monsoon (EAWM) change. The material supply of core SCS18-1 is mainly controlled by solar radiation in the Northern Hemisphere.